Kinerja Pegawai Pada Kantor Badan Pendapatan Daerah Kabupaten Sikka - Serafia Ohin Niron; Andreas Rengga; Yustina Olivia Da Silva (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This research was grounded on the issue of the problem of employee performance at the Sikka Regency Regional Revenue Agency Office from the aspect of Work Supervision and Coordination. This research aimed : (1) determine the description of Employee Performance, Work Supervision, and Coordination (2) analyze the effect of Work Supervision and Coordinating on Employee Performance both partially and simultaneously.The population in this research was 50 employees of the Sikka Regency Regional Revenue Agency Affice. Using the slovin formula, the sample in this research was 50 employees. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing was carried out through the F-test and T-test. The results of the descriptive analysis showed that the Employee Performance variable was in the good criteria, the Work Supervision variable was in the good criteria, and the Coordination variable was in the very good criteria. The statistical results of the t-test show that partially the Work Supervision variable has a positive and significant effect on Employee Performance. Furthermore, the Coordination variable has a positive and significant effect on Employee Performance. The statistical results of the F-test showed that the Work Supervision and Coordination variables had a significant effect on Employee Performance simultaneously. The results of the determination analysis show that the two independent variables in this research can explain the fluctuation of Employee Performance at the Sikka Regency Regional Revenue Agency Office by 0,404%.